Steel plate and its manufacturing method

By increasing the unevenness of the steel plate surface, the grease is easier to be distributed to the steel plate surface during the cold pressing process, thereby improving friction, reducing mold damage, and extending mold life, solving the problem of mold damage and life during the cold pressing of steel plates in the prior art.

JP7662963B2Active Publication Date: 2025-04-16NIPPON STEEL CORPORATION
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
JP2023510584
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-02
Filing Date
2022-02-07
Publication Date
2025-04-16
Estimated Expiration
2042-02-07

AI Technical Summary

Technical Problem

The prior art still has room for improvement in improving the mold damage and mold life of high-strength steel plates during cold pressing.

Method used

By increasing the unevenness of the steel plate surface, grease is easier to be distributed to the steel plate surface during the cold pressing process, thereby improving friction, reducing mold damage, and extending mold life. The specific method is to adjust the hot rolling conditions to increase the surface unevenness and perform incompletely smooth baking treatment after hot rolling.

Benefits of technology

It effectively reduces the damage to the mold during cold pressing, extends the service life of the mold, and improves the surface characteristics of the steel plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662963000013
    Figure 0007662963000013
  • Figure 0007662963000014
    Figure 0007662963000014
  • Figure 0007662963000015
    Figure 0007662963000015
Patent Text Reader

Abstract

Disclosed in a steel sheet that makes it possible to reduce damage to a mold during cold pressing, that has a predetermined chemical composition and steel structure, and wherein a plurality of steps having a height difference exceeding 5.0 μm are present at intervals of 2.0 mm or less in the sheet surface.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to a steel sheet and a method for manufacturing the same.

[0002] In recent years, efforts to reduce the weight of automobile bodies have been made by applying high-strength steel sheets in order to improve the fuel efficiency of automobiles. Also, to ensure the safety of passengers, high-strength steel sheets are increasingly being used in automobile bodies instead of mild steel sheets. In order to further reduce the weight of automobile bodies in the future, the strength level of high-strength steel sheets must be increased more than ever before.

[0003] Automobile parts are formed by die pressing, and the parts are formed by cold die pressing or hot die pressing. In the case of cold pressing, as the strength of the steel plate increases, the surface pressure during pressing increases, and the die life is reduced, which is a problem. However, in the prior art, although the improvement of the workability of the steel plate by softening the steel plate has been studied (for example, Patent Documents 1 to 3 below), there is still room for improvement in reducing damage to the die during cold pressing of the steel plate and increasing the die life.

[0004] Patent Document 1 discloses a method for inexpensively producing a high-carbon cold-rolled steel strip that is softened and has excellent workability while preventing the occurrence of seizing defects, by cold rolling a hot-rolled steel strip containing 0.3-1.3% C, 0.03-0.35% Si, and 0.20-1.50% Mn, with the balance being essentially Fe and unavoidable impurities, at a rolling reduction of 20% to 85%, and then annealing the strip in a bell-type batch annealing furnace in a gas atmosphere containing 75% or more by volume of hydrogen and the balance being essentially nitrogen and unavoidable impurities, at a heating rate of 20-100°C / Hr to Ac1 point to Ac1 point + 50°C, holding the steel soaked for 8 hours or less, and then cooling to Ar1 point or less at a cooling rate of 50°C / Hr or less.

[0005] Patent Document 2 discloses a steel sheet for processing having excellent paint clarity, characterized in that the surface of the steel sheet is formed into an uneven rough surface, the wavelength λ of the uneven pattern on the rough surface is set to 500 μm or less, and the center line average roughness Ra is set to the range of 1 to 5 μm.

[0006] Patent Document 3 discloses a steel sheet and a manufacturing method thereof, which has a predetermined chemical composition and a metal structure containing, by area ratio, 40.0% or more and less than 60.0% polygonal ferrite, 30.0% or more bainitic ferrite, 10.0% or more and 25.0% or less retained austenite, and 15.0% or less martensite, wherein the retained austenite has an aspect ratio of 2.0 or less, a major axis length of 1.0 μm or less and a minor axis length of 1.0 μm or less, and the proportion of the retained austenite is 80.0% or more, the aspect ratio of the bainitic ferrite is 1.7 or less and the proportion of bainitic ferrite in which the average crystal orientation misorientation of regions surrounded by grain boundaries having a crystal orientation misorientation of 15° or more is 0.5° or more and less than 3.0° is 80.0% or more, and the connectivity D value between the martensite, the bainitic ferrite, and the retained austenite is 0.70 or less. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-204540 [Patent Document 2] Japanese Patent Application Publication No. 4-253503 [Patent Document 3] Patent No. 6791838 Summary of the Invention [Problem to be solved by the invention]

[0008] In view of the above circumstances, the present application discloses a steel sheet capable of reducing damage to a die during cold pressing and increasing the life of the die, and a method for manufacturing the same. [Means for solving the problem]

[0009] The inventors have conducted extensive research into methods for solving the above problems and have confirmed that by increasing the surface roughness of a steel sheet compared to conventional materials, oil can be applied to the steel sheet surface during cold pressing, thereby increasing lubricity and reducing die damage during high surface pressure cold pressing. Therefore, by increasing the roughness of the steel sheet surface, it is possible to extend the life of the press die.

[0010] The present inventors have also found that the above-mentioned steel sheet can be manufactured by an integrated manufacturing method characterized by increasing the surface irregularities of the hot-rolled sheet by adjusting the hot-rolling conditions, and then carrying out an annealing process without completely smoothing out the irregularities.

[0011] Furthermore, the inventors have discovered through accumulating various research that a steel sheet having the above-mentioned surface irregularities that causes less damage to press dies and extends the life of the dies is difficult to manufacture by simply devising a single hot rolling condition or annealing condition, etc., and can only be manufactured by achieving optimization in a so-called integrated process that includes the hot rolling and annealing steps.

[0012] The gist of the present invention is as follows. (1) In mass%, C: 0.15-0.35%, Si: 0.01 to 2.00%, Mn: 0.10-4.00%, P:0.0200% or less, S: 0.0200% or less, Al: 0.001 to 1.000%, N: 0.0200% or less, Ti: 0 to 0.500%, Co: 0 to 0.500%, Ni: 0 to 0.500%, Mo: 0 to 0.500%, Cr: 0~2.000%, O: 0 to 0.0100%, B: 0~0.0100%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0-0.500%, W: 0~0.1000%, Ta: 0 to 0.1000%, Sn: 0 to 0.0500%, Sb: 0 to 0.0500%, As: 0~0.0500%, Mg: 0 to 0.0500%, Ca: 0 to 0.0500%, Y: 0 to 0.0500%, Zr: 0 to 0.0500%, La: 0 to 0.0500%, and Ce: 0 to 0.0500%, and the balance being Fe and impurities, In terms of area ratio, Total of martensite and tempered martensite: 90.0% or more, The sum of ferrite, pearlite and bainite: 0% to 10.0%; and Retained austenite: 0% to 5.0% The steel structure comprises There are multiple steps on the plate surface with a height difference of more than 5.0 μm spaced 2.0 mm or less apart. steel plate. (2) In mass%, Ti: 0.001 to 0.500%, Co: 0.001 to 0.500%, Ni: 0.001 to 0.500%, Mo: 0.001 to 0.500%, Cr: 0.001~2.000% O: 0.0001 to 0.0100% B: 0.0001~0.0100%, Nb: 0.001 to 0.500%, V: 0.001 to 0.500%, Cu: 0.001 to 0.500%, W: 0.0001 to 0.1000%, Ta: 0.0001 to 0.1000%, Sn: 0.0001~0.0500%, Sb: 0.0001 to 0.0500%, As: 0.0001 to 0.0500%, Mg: 0.0001 to 0.0500%, Ca: 0.0001 to 0.0500%, Y: 0.0001 to 0.0500%, Zr: 0.0001 to 0.0500%, La: 0.0001 to 0.0500%, and Ce: 0.0001 to 0.0500%, The chemical composition contains one or more of the following: The steel plate according to (1) above. (3) A method for manufacturing a steel sheet, comprising the steps of: hot rolling a steel slab having the chemical composition described in (1) or (2) above to obtain a hot rolled sheet; coiling the hot-rolled sheet; Pickling the hot-rolled sheet; and Annealing the hot-rolled sheet without cold rolling, or annealing the hot-rolled sheet after cold rolling; Including, The hot rolling includes rolling the plate at a reduction ratio of more than 30% and not more than 70% while supplying a lubricant between a rolling roll and the plate in a stand one before a final stand of a finishing mill; The temperature when the hot-rolled sheet is coiled is 700° C. or less, When the cold rolling is performed, the rolling reduction rate in the cold rolling is 0.1 to 20%. Manufacturing method of steel plate. Effect of the Invention

[0013] The steel sheet according to the present disclosure can reduce damage to dies during cold pressing and extend the life of the dies, i.e., the steel sheet according to the present disclosure is suitable as a steel sheet for cold press working. [Brief description of the drawings]

[0014] [Figure 1] Schematic diagram of the morphology of steps on the steel sheet surface. [Diagram 2] FIG. 2 is a schematic diagram for explaining the difference between the "maximum height roughness Rz" and the "step" referred to in the present application. [Diagram 3] FIG. 2 is a schematic diagram for explaining the measurement conditions for sliding friction resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, embodiments of the present invention will be described. Note that these descriptions are intended to be merely examples of the embodiments of the present invention, and the present invention is not limited to the following embodiments.

[0016] <Steel plate> The steel sheet according to this embodiment has, in mass%, C: 0.15-0.35%, Si: 0.01 to 2.00%, Mn: 0.10-4.00%, P:0.0200% or less, S: 0.0200% or less, Al: 0.001 to 1.000%, N: 0.0200% or less, Ti: 0 to 0.500%, Co: 0 to 0.500%, Ni: 0 to 0.500%, Mo: 0 to 0.500%, Cr: 0~2.000%, O: 0 to 0.0100%, B: 0~0.0100%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0 to 0.500%, W: 0~0.1000%, Ta: 0 to 0.1000%, Sn: 0 to 0.0500%, Sb: 0 to 0.0500%, As: 0~0.0500%, Mg: 0 to 0.0500%, Ca: 0 to 0.0500%, Y: 0 to 0.0500%, Zr: 0 to 0.0500%, La: 0 to 0.0500%, and Ce: 0 to 0.0500%, and the balance being Fe and impurities, In terms of area ratio, Total of martensite and tempered martensite: 90.0% or more, The sum of ferrite, pearlite and bainite: 0% to 10.0%; and Retained austenite: 0% to 5.0% The steel structure comprises The plate surface is characterized by the presence of multiple steps with a height difference of more than 5.0 μm spaced apart by 2.0 mm or less.

[0017] First, the reason for limiting the chemical composition of the steel sheet according to the embodiment of the present invention will be described. Here, "%" for the components means mass%. Furthermore, in this specification, "to" indicating a numerical range is used to mean that the numerical values ​​before and after it are included as the lower and upper limits, unless otherwise specified.

[0018] (C: 0.15~0.35%) C is an element that inexpensively increases tensile strength, and is an extremely important element for suppressing the transformation from austenite to ferrite, bainite, and pearlite in the continuous annealing process and controlling the strength of steel. When the C content is 0.05% or more, such effects are easily obtained, and particularly when the C content is 0.15% or more, more remarkable effects are easily obtained. The C content may be 0.20% or more. On the other hand, excessive C content deteriorates elongation and hole expandability, and makes it difficult to obtain the desired surface unevenness in hot rolling, which may promote mold damage during cold pressing of the steel sheet. When the C content is 0.35% or less, such problems are easily avoided. The C content may be 0.30% or less.

[0019] (Si: 0.01 to 2.00%) Si acts as a deoxidizer and is an element that suppresses the precipitation of carbides during the cooling process during cold rolling annealing. When the Si content is 0.01% or more, such an effect is easily obtained. The Si content may be 0.10% or more. On the other hand, excessive Si content increases the steel strength and reduces the workability, and further, coarse oxides are dispersed in the surface layer of the hot-rolled sheet, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. When the Si content is 2.00% or less, such problems are easily avoided. The Si content may be 1.60% or less.

[0020] (Mn: 0.10-4.00%) Mn is a factor that affects the ferrite transformation of steel and is an element that is effective in increasing strength. When the Mn content is 0.10% or more, such an effect is easily obtained. The Mn content may be 0.60% or more. On the other hand, excessive Mn content increases the strength of the steel and reduces the workability, and further, coarse oxides are dispersed in the surface layer of the hot-rolled sheet, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. When the Mn content is 4.00% or less, such problems are easily avoided. The Mn content may be 3.00% or less.

[0021] (P:0.0200% or less) P is an element that promotes Mn concentration in unsolidified parts during the solidification process of molten steel, lowers the Mn concentration in negative segregation parts, and promotes an increase in the area ratio of ferrite, and the less P, the better. In addition, excessive P content increases the strength of the steel and leads to brittle fracture of the steel, which may deteriorate formability such as elongation and hole expansion. The P content may be 0%, 0.0001% or more, 0.0010% or more, 0.0200% or less, or 0.0180% or less.

[0022] (S:0.0200% or less) S is an element that generates nonmetallic inclusions such as MnS in steel and reduces the ductility of steel parts, so the less S, the better. In addition, excessive S content leads to deterioration of formability such as elongation and hole expansion, and makes it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote mold damage during cold pressing of the steel sheet. The S content may be 0%, 0.0001% or more, 0.0005% or more, 0.0200% or less, or 0.0180% or less.

[0023] (Al: 0.001 to 1.000%) Al is an element that acts as a deoxidizer for steel and stabilizes ferrite, and is added as necessary. When the Al content is 0.001% or more, such an effect is easily obtained. The Al content may be 0.010% or more. On the other hand, when Al is contained excessively, ferrite transformation and bainite transformation during the cooling process in annealing may be excessively promoted, and the strength of the steel sheet may decrease. In addition, when Al is contained excessively, coarse and large amounts of Al oxides may be generated on the steel sheet surface during hot rolling, making it difficult to obtain the desired unevenness on the steel sheet surface. When the Al content is 1.000% or less, such problems are easily avoided. The Al content may be 0.800% or less.

[0024] (N:0.0200% or less) N is an element that forms coarse nitrides in steel sheets and reduces the workability of the steel sheets. N is also an element that causes blowholes during welding. Excessive N content combines with Al and Ti to generate a large amount of AlN or TiN, and these nitrides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the mold during cold pressing of the steel sheet. The N content may be 0%, 0.0001% or more, 0.0010% or more, 0.0200% or less, or 0.0160% or less.

[0025] The basic chemical composition of the steel sheet in this embodiment is as described above. Furthermore, the steel sheet in this embodiment may contain at least one of the following optional elements as necessary. These elements do not necessarily have to be contained, so the lower limit is 0%.

[0026] (Ti: 0 to 0.500%) Ti is a strengthening element. It contributes to increasing the strength of steel sheets through precipitation strengthening, fine grain strengthening by inhibiting the growth of crystal grains, and dislocation strengthening through inhibiting recrystallization. On the other hand, excessive Ti content increases the precipitation of coarse carbides, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the mold during cold press molding of the steel sheet. The Ti content may be 0%, 0.001% or more, 0.005% or more, 0.500% or less, or 0.400% or less.

[0027] (Co: 0 to 0.500%) Co is an element effective in controlling the morphology of carbides and increasing strength, and is added as necessary to control strength. On the other hand, when Co is contained in an excessive amount, a large number of fine Co carbides are precipitated, and these carbides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the mold during cold pressing of the steel sheet. The Co content may be 0%, 0.001% or more, and may be 0.500% or less, or 0.400% or less.

[0028] (Ni: 0~0.500%) Ni is a strengthening element and is effective in improving hardenability. In addition, Ni may be added because it improves the wettability between the steel sheet and the plating and promotes the alloying reaction. On the other hand, excessive Ni content affects the peelability of oxide scale during hot rolling, promotes the generation of scratches on the steel sheet surface, makes it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, and may promote damage to the mold during cold pressing of the steel sheet. The Ni content may be 0%, 0.001% or more, and may be 0.500% or less, or 0.400% or less.

[0029] (Mo:0~0.500%) Mo is an element effective in improving the strength of steel sheets. Mo is also an element that has the effect of suppressing ferrite transformation that occurs during heat treatment in continuous annealing equipment or continuous hot-dip galvanizing equipment. On the other hand, if Mo is contained excessively, a large number of fine Mo carbides are precipitated, and these carbides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the mold during cold pressing of the steel sheet. The Mo content may be 0%, 0.001% or more, and may be 0.500% or less, or 0.400% or less.

[0030] (Cr:0~2.000%) Cr, like Mn, is an element that suppresses pearlite transformation and is effective in increasing the strength of steel, and is added as necessary. On the other hand, excessive Cr content promotes the formation of retained austenite, and the presence of excess retained austenite may lead to a decrease in hole expandability. The Cr content may be 0%, 0.001% or more, 2.000% or less, or 1.500% or less.

[0031] (O:0~0.0100%) Since O forms oxides and deteriorates workability, it is necessary to suppress the content. In particular, oxides often exist as inclusions, and if granular coarse oxides exist on the surface of the steel sheet, they cause cracks on the surface of the steel sheet and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling and annealing. Furthermore, if they exist on the punched end surface or cut surface, they form notch-like scratches or coarse dimples on the end surface, which may lead to a decrease in hole expandability. The O content may be 0.0100% or less, or may be 0.0080% or less. The O content may be 0%, but controlling the O content to less than 0.0001% may increase the refining time and increase the manufacturing cost. In order to prevent an increase in manufacturing costs, the O content may be 0.0001% or more, or may be 0.0010% or more.

[0032] (B: 0~0.0100%) B is an element that suppresses the formation of ferrite and pearlite during the cooling process from austenite and promotes the formation of low-temperature transformation structures such as bainite or martensite. In addition, B is an element that is beneficial for increasing the strength of steel and is added as necessary. On the other hand, excessive B content leads to the formation of coarse B oxides in the steel, and the B oxides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, these oxides become the starting point of void generation and facilitate the progression of fracture, which may lead to a decrease in hole expandability. The B content may be 0%, 0.0001% or more, 0.0010% or more, 0.0100% or less, or 0.0080% or less.

[0033] (Nb: 0~0.500%) Nb is an element effective in controlling the morphology of carbides, and its addition refines the structure, so it is also effective in improving toughness. On the other hand, if Nb is contained excessively, a large number of fine and hard Nb carbides are precipitated, and these carbides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, these carbides become the starting point of fracture, which may lead to a decrease in hole expandability. The Nb content may be 0%, 0.001% or more, or 0.500% or less, or 0.400% or less.

[0034] (V:0~0.500%) V is a strengthening element. It contributes to increasing the strength of the steel sheet through precipitation strengthening, fine grain strengthening by inhibiting the growth of ferrite crystal grains, and dislocation strengthening through inhibiting recrystallization. On the other hand, excessive V content increases the precipitation of carbonitrides, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, these carbides become the starting point of fracture, which may lead to a decrease in hole expandability. The V content may be 0%, 0.001% or more, and may be 0.500% or less, or 0.400% or less.

[0035] (Cu: 0~0.500%) Cu is an element effective in improving the strength of steel sheets. On the other hand, if Cu is contained excessively, the steel material becomes embrittled during hot rolling, making hot rolling impossible. Furthermore, the Cu layer concentrated on the steel sheet surface suppresses contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the mold during cold pressing of the steel sheet. The Cu content may be 0%, 0.001% or more, 0.500% or less, or 0.400% or less.

[0036] (W:0~0.1000%) W is effective in increasing the strength of steel sheets, and precipitates and crystallized materials containing W become hydrogen trapping sites. On the other hand, excessive W content generates coarse carbides, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, since the breakage easily progresses from the coarse carbides, it may lead to a decrease in hole expandability. The W content may be 0%, 0.0001% or more, 0.0010% or more, 0.1000% or less, or 0.0800% or less.

[0037] (Ta: 0 to 0.1000%) Ta, like Nb, V, and W, is an element effective in controlling the morphology of carbides and increasing strength, and is added as necessary. On the other hand, if Ta is contained excessively, a large number of fine Ta carbides are precipitated, and these carbides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, since the progress of fracture is facilitated from these carbides as starting points, it may lead to a decrease in hole expandability. The Ta content may be 0%, 0.0001% or more, 0.0010% or more, 0.1000% or less, or 0.0800% or less.

[0038] (Sn: 0~0.0500%) Sn is an element contained in steel when scrap is used as a raw material, and the less the better. Excessive Sn content may cause cracks on the surface of the steel sheet and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, and may promote damage to the die during cold pressing of the steel sheet. In addition, it may cause a decrease in hole expandability due to embrittlement of the steel sheet. The Sn content may be 0.0500% or less, or may be 0.0400% or less. The Sn content may be 0%, but controlling the Sn content to less than 0.0001% may increase the refining time and increase the manufacturing cost. In order to prevent an increase in manufacturing costs, the Sn content may be 0.0001% or more, or may be 0.0010% or more.

[0039] (Sb: 0~0.0500%) Sb, like Sn, is an element contained when scrap is used as a steel raw material. Sb strongly segregates at grain boundaries, which leads to embrittlement of the grain boundaries and a decrease in ductility, so the less Sb, the better. In addition, excessive Sb content can cause cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, and can promote damage to the die during cold pressing of the steel sheet. In addition, it can cause a decrease in hole expandability due to embrittlement of the steel sheet. The Sb content can be 0.0500% or less, or 0.0400% or less. The Sb content can be 0%, but controlling the Sn content to less than 0.0001% may increase the refining time and increase the manufacturing cost. In order to prevent an increase in manufacturing costs, the Sb content can be 0.0001% or more, or 0.0010% or more.

[0040] (As:0~0.0500%) Like Sn and Sb, As is an element that is contained when scrap is used as a steel raw material and strongly segregates at grain boundaries, and the less the better. In addition, excessive As content may cause cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, and may promote damage to the die during cold pressing of the steel sheet. In addition, it may cause a decrease in hole expandability due to embrittlement of the steel sheet. The As content may be 0.0500% or less, or may be 0.0400% or less. The As content may be 0%, but controlling the As content to less than 0.0001% may increase the refining time and increase the manufacturing cost. In order to prevent an increase in manufacturing costs, the As content may be 0.0001% or more, or may be 0.0010% or more.

[0041] (Mg: 0~0.0500%) Mg is an element that can control the form of sulfides by adding a small amount, and is added as necessary. On the other hand, if Mg is contained excessively, coarse inclusions are formed, and the inclusions suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, it may cause a decrease in hole expandability due to embrittlement of the steel sheet. The Mg content may be 0%, 0.0001% or more, 0.0010% or more, 0.0500% or less, or 0.0400% or less.

[0042] (Ca: 0~0.0500%) Ca is useful as a deoxidizing element and is also effective in controlling the morphology of sulfides. On the other hand, excessive Ca content can cause cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, and can promote damage to the mold during cold pressing of the steel sheet. The Ca content may be 0%, 0.0001% or more, 0.0010% or more, 0.0500% or less, or 0.0400% or less.

[0043] (Y:0~0.0500%) Y is an element that can control the form of sulfides by adding a small amount, like Mg and Ca, and is added as necessary. On the other hand, if Y is contained excessively, coarse Y oxides are generated, and the Y oxides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, these oxides may become the starting point of fracture, which may lead to a decrease in hole expandability. The Y content may be 0%, 0.0001% or more, 0.0010% or more, 0.0500% or less, or 0.0400% or less.

[0044] (Zr: 0~0.0500%) Zr is an element that can control the form of sulfides by adding a small amount, similar to Mg, Ca, and Y, and is added as necessary. On the other hand, if Zr is contained excessively, coarse Zr oxides are generated, and the Zr oxides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, these oxides become the starting point of fracture, which may lead to a decrease in hole expandability. The Zr content may be 0%, 0.0001% or more, 0.0010% or more, 0.0500% or less, or 0.0400% or less.

[0045] (La:0~0.0500%) La is an element that is effective in controlling the morphology of sulfides when added in small amounts, and is added as necessary. On the other hand, when La is contained excessively, La oxides are generated, and the La oxides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, these oxides become the starting point of fracture, which may lead to a decrease in hole expandability. The La content may be 0%, 0.0001% or more, 0.0010% or more, and 0.0500% or less, or 0.0400% or less.

[0046] (Ce: 0~0.0500%) Ce is an element that can control the form of sulfides by adding a small amount, similar to La, and is added as necessary. On the other hand, if Ce is contained excessively, Ce oxide is generated, and the Ce oxide suppresses the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may promote damage to the die during cold pressing of the steel sheet. In addition, these oxides become the starting point of fracture, which may lead to a decrease in hole expandability. The Ce content may be 0%, 0.0001% or more, 0.0010% or more, 0.0500% or less, or 0.0400% or less.

[0047] In the steel sheet according to the present embodiment, the balance of the above-mentioned components is Fe and impurities. The impurities are components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, when the steel sheet according to the present embodiment is industrially manufactured.

[0048] Next, the characteristics of the structure and properties of the steel plate according to the embodiment of the present invention will be described.

[0049] (Total area ratio of martensite and tempered martensite: 90.0% or more) The total area fraction of martensite and tempered martensite is an effective structure for improving the strength of the steel sheet. In addition, when the area fraction of martensite and structures softer than tempered martensite increases, the area where the difference in hardness between structures is large increases, and hole expandability deteriorates. The area fraction of martensite and tempered martensite may be 90.0% or more, preferably 95.0% or more. There is no particular upper limit, and it may be 100%.

[0050] (Total area ratio of ferrite, pearlite and bainite: 0% to 10.0%) Ferrite, pearlite and bainite are softer structures than martensite and tempered martensite. These structures are effective in improving the strength-ductility balance of steel sheets, but because they are softer than martensite and tempered martensite, the hardness difference is large, voids are likely to occur at the interface between them during deformation, and hole expandability is reduced. Therefore, the smaller the total area ratio of ferrite, pearlite and bainite, the more preferable it is. The total area ratio of ferrite, pearlite and bainite may be 0%, 1.0% or more, 10.0% or less, 5.0% or less, or 3.0% or less. Although the productivity is somewhat reduced, it is possible to make the total area ratio of ferrite, pearlite and bainite 0% by controlling the integrated manufacturing conditions with high precision.

[0051] (Area ratio of retained austenite: 0% to 5.0%) The area ratio of the retained austenite is an effective structure for improving the strength-ductility balance of the steel sheet. On the other hand, if the area ratio of the retained austenite is too large, the proportion of chemically unstable austenite increases, and processing-induced transformation occurs during deformation, which may lead to a decrease in hole expandability. The area ratio of the retained austenite may be 0%, 1.0% or more, 5.0% or less, or 3.0% or less.

[0052] (Surface unevenness) The distribution interval of the steps having a height difference of more than 5.0 μm on the steel sheet surface contributes to the amount of oil carried over during press working, suppresses damage to the die during press forming, and is important for improving the die life. The shorter the distribution interval, the more preferable it is, but if the distribution interval is less than 0.01 mm, the steel sheet surface may have a sawtooth shape. In this regard, the interval may be 0.01 mm or more, or 0.05 mm or more. On the other hand, if it exceeds 2.0 mm, it may be difficult to obtain the effect of suppressing the above-mentioned die damage, and it may be difficult to improve the die life. In this regard, the interval may be 2.0 mm or less, 1.8 mm or less, 1.5 mm or less, 1.2 mm or less, 1.0 mm or less, 0.7 mm or less, or 0.4 mm or less. In addition, in the steel sheet according to this embodiment, it is necessary that a plurality of steps having a height difference of more than 5.0 μm are distributed on the steel sheet surface at the above interval. The height difference may be 7.0 μm or more, or 10.0 μm or more. The upper limit of the height difference of the steps is not particularly limited, and may be, for example, 20.0 μm or less, 15.0 μm or less, or 10.0 μm or less. In the steel sheet according to the present embodiment, a plurality of steps having a height difference of more than 5.0 μm may be present at intervals of 2.0 mm or less over 50 area% or more, 60 area% or more, 70 area% or more, 80 area% or more, or 90 area% or more of the steel sheet surface.

[0053] FIG. 1 shows an example of a "step having a height difference of more than 5.0 μm". FIG. 1 shows the shape of the step when observing the cross section of the steel sheet in the thickness direction. As shown in FIG. 1, the steel sheet surface may have repeated unevenness in the rolling direction, and the height difference of the step specified by each unevenness exceeds 5.0 μm, and the step is included in a range of 2.0 mm or less, that is, the interval between the steps is 2.0 mm or less. In the present invention, so-called negative angle parts (undercut parts) may be present in at least some of the steps among the multiple steps. In the present invention, the heights of the multiple steps may be different from each other, for example, the heights of each may be irregularly (randomly) different. In addition, the shapes of the multiple steps may be different from each other. In addition, the intervals between the multiple steps may be irregularly (randomly) instead of being constant. Such a step shape can be formed by a method described later.

[0054] In addition, the "step having a height difference of more than 5.0 μm" in the present application is a concept different from general surface roughness such as maximum height roughness Rz and arithmetic mean roughness Ra. For example, the "maximum height roughness Rz" means the distance between the most convex part and the most concave part of the surface unevenness (maximum difference in height), as shown in FIG. 2(A), and the distribution (spacing) of the surface unevenness cannot be specified from the "maximum height roughness Rz". In addition, the "arithmetic mean roughness Ra" is merely an average value of the surface roughness, and its maximum value is unknown, and the distribution (spacing) of the surface unevenness cannot be specified from the "arithmetic mean roughness Ra". In contrast, the "step having a height difference of more than 5.0 μm" in the present application means that the height difference of "one step" exceeds 5.0 μm, as shown in FIG. 2(B), and the step must exist in a plurality of steps spaced 2.0 mm or less apart.

[0055] (Tensile strength) In order to reduce the weight of a structure using steel as a material and to improve the resistance of the structure to plastic deformation, it is preferable that the steel material has a large work hardening ability and exhibits maximum strength. On the other hand, if the tensile strength is too high, it may be prone to fracture with low energy during plastic deformation, and formability may be reduced. The tensile strength of the steel plate is not particularly limited, but may be 1300 MPa or more, 1400 MPa or more, 2100 MPa or less, 2000 MPa or less, or 1900 MPa or less.

[0056] (Total elongation) When manufacturing a structure by cold forming a steel sheet as a raw material, elongation is required to finish the structure into a complex shape. If the total elongation is too low, the raw material may crack during cold forming. On the other hand, the higher the total elongation, the better, but if the total elongation is excessively increased, a large amount of retained austenite is required in the steel structure, which may result in a decrease in hole expandability. The total elongation of the steel sheet is not particularly limited, but may be 5% or more, 8% or more, 18% or less, or 15% or less.

[0057] (Hole expandability) When manufacturing a structure by cold forming a steel sheet as a material, hole expandability is required as well as elongation in order to finish the structure into a complex shape. If the hole expandability is too small, the material may crack during cold forming. The hole expansion ratio of the steel sheet is not particularly limited, but may be 20% or more, 25% or more, 90% or less, or 80% or less.

[0058] (Sliding friction resistance) In order to suppress damage to the die during cold press molding of the steel sheet, it is preferable that the sliding friction resistance of the steel sheet is 1.0 or less. If the sliding friction resistance is too large, friction during press molding increases, and the die life may be shortened. The sliding friction resistance may be 0.8 or less, or may be 0.6 or less. The lower limit of the sliding friction resistance is not particularly limited.

[0059] (Thickness) The plate thickness is a factor that affects the rigidity of the steel member after forming, and the greater the plate thickness, the higher the rigidity of the member. If the plate thickness is too small, the rigidity will decrease, and press formability may decrease due to the influence of unavoidable non-ferrous inclusions present inside the steel plate. On the other hand, if the plate thickness is too large, the press forming load will increase, leading to wear of the mold and a decrease in productivity. The plate thickness of the steel plate is not particularly limited, but may be 0.2 mm or more and 6.0 mm or less. In addition, the "steel plate" referred to in this application may be a single-layer steel plate. Here, the "single-layer steel plate" means that it is not a so-called multi-layer steel plate, and refers to a steel plate in which the joint interface between the base steel plates is not observed in the plate thickness direction when the cross section of the steel plate is observed. For example, it is a steel plate consisting of one slab. The "plate thickness" of the above steel plate may be the plate thickness as a single-layer steel plate. In addition, the single-layer steel plate may have a surface treatment layer such as a plating layer formed on its surface. That is, the "steel plate" referred to in the present application may be a steel plate having a single layer and a surface treatment layer.

[0060] Next, the methods for observing and measuring the above-specified structure, and the methods for measuring and evaluating the above-specified characteristics will be described.

[0061] (Method for measuring the total area ratio of ferrite, pearlite, and bainite) The structure observation is performed using a scanning electron microscope (SEM). Prior to the observation, the sample for structure observation is wet-polished with emery paper and polished with diamond abrasives with an average particle size of 1 μm, the observation surface is mirror-finished, and the structure is etched with a 3% nitric acid alcohol solution. The magnification of the observation is 3000 times, and 10 random images are taken of a 30 μm x 40 μm field of view at each 1 / 4 thickness position from the surface side of the steel plate. The structure ratio is calculated using a point counting method. A total of 100 lattice points are set at intervals of 3 μm vertically and 4 μm horizontally for the obtained structure image, and the structure present under the lattice points is identified, and the structure ratio contained in the steel material is calculated from the average value of the 10 images. Ferrite is a blocky crystal grain that does not contain iron-based carbides with a major axis of 100 nm or more inside. Bainite is a collection of lath-shaped crystal grains that does not contain iron-based carbides with a long diameter of 20 nm or more, or that contains iron-based carbides with a long diameter of 20 nm or more and the carbides belong to a single variant, i.e., a group of iron-based carbides elongated in the same direction. Here, a group of iron-based carbides elongated in the same direction means that the difference in the elongation direction of the iron-based carbides is within 5°. Bainite grains are counted as bainite surrounded by grain boundaries with an orientation difference of 15° or more. Here, the "grain boundaries with an orientation difference of 15° or more" are obtained using SEM-EBSD in the following procedure. Prior to the SEM-EBSD measurement, the observation surface of the measurement sample is polished to a mirror finish, and further distortion caused by polishing is removed. As in the above SEM observation, a field of view of 30 μm × 40 μm is set as the measurement range at each 1 / 4 position of the thickness from the surface side of the steel plate, and crystal orientation data of BCC iron is obtained by SEM-EBSD. The EBSD measurement is performed using an EBSD detector attached to the SEM, and the measurement interval (STEP) is 0.05 μm. In this case, in the present invention, the software "OIMDataCollectionTM (ver.7)" manufactured by TSL Solutions Co., Ltd. is used as the data acquisition software for the crystal orientation. In the crystal orientation MAP data of BCC iron obtained under these measurement conditions, the boundaries with a crystal orientation difference of 15° or more are identified as crystal grain boundaries, except for the region with a confidence value (CI value) of less than 0.1.Bainite can be said to be a mixed structure of bainitic ferrite, which is made up of a body-centered cubic structure of iron, and iron-based carbide (Fe3C). Bainitic ferrite is distinguished from the above-mentioned ferrite. Pearlite is a structure that contains cementite precipitated in rows, and the area that is photographed with bright contrast in the secondary electron image is considered to be pearlite, and the area ratio is calculated.

[0062] (Method for measuring area ratio of martensite and tempered martensite) Martensite and tempered martensite are observed with scanning and transmission electron microscopes, and those containing Fe-based carbides inside are identified as tempered martensite, and those containing almost no carbides are identified as martensite. Fe-based carbides with various crystal structures have been reported, and any Fe-based carbide may be included. Depending on the heat treatment conditions, multiple types of Fe-based carbides may be present.

[0063] (Method for measuring area ratio of retained austenite) The area fraction of retained austenite is determined by X-ray measurement as follows. First, the portion from the surface of the steel plate to 1 / 4 of the thickness of the steel plate is removed by mechanical polishing and chemical polishing, and the chemically polished surface is measured using MoKα rays as characteristic X-rays. Then, the area fraction of retained austenite in the center of the plate thickness is calculated using the following formula from the integrated intensity ratio of the diffraction peaks of (200) and (211) of the body-centered cubic lattice (bcc) phase and (200), (220), and (311) of the face-centered cubic lattice (fcc) phase. Sγ=(I200f+I220f+I311f) / (I200b+I211b)×100 (Sγ is the area fraction of retained austenite at the center of the sheet thickness, I200f, I220f, and I311f indicate the intensities of the (200), (220), and (311) diffraction peaks of the fcc phase, respectively, and I200b and I211b indicate the intensities of the (200) and (211) diffraction peaks of the bcc phase, respectively.)

[0064] The sample to be subjected to X-ray diffraction is prepared by reducing the thickness of the steel plate from the surface to a predetermined thickness by mechanical polishing, etc., and then removing distortion by chemical polishing or electrolytic polishing, etc., and adjusting the sample according to the above-mentioned method so that an appropriate surface becomes the measurement surface within the range of 1 / 8 to 3 / 8 of the plate thickness. Naturally, the material anisotropy is further reduced by satisfying the above-mentioned X-ray intensity limit not only in the vicinity of 1 / 4 of the plate thickness but also for as many thicknesses as possible. However, by measuring 1 / 8 to 3 / 8 of the plate surface, the material properties of the entire steel plate can be roughly represented. Therefore, the measurement range is specified as 1 / 8 to 3 / 8 of the plate thickness.

[0065] (Method of measuring the distance between surface irregularities (steps with height difference of more than 5.0 μm)) The height difference and distribution interval of the unevenness on the steel sheet surface are measured using a scanning electron microscope (FE-SEM: Field Emission Scanning Electron Microscope). Prior to observation using SEM, a sample for microstructural observation with a length in the rolling direction of more than 20 mm is embedded in resin, and the surface parallel to the rolling direction and perpendicular to the sheet thickness direction (TD surface: Transversal Direction surface) is polished to a mirror finish. The SEM observation magnification is set to 1000 times, and a field of view that includes both the steel sheet and resin within an observation range that is more than 110 μm in the rolling direction and more than 70 μm in the sheet thickness direction is obtained over a rolling length of 20 mm, and a series of photographs that capture the unevenness on the steel sheet surface are obtained. In this continuous photograph, a location where the height difference of the unevenness on the steel sheet surface exceeds 5 μm within a length of 20 μm in the rolling direction is defined as "a step having a height difference of more than 5.0 μm on the steel sheet surface," and the average distance between the tops of the steps within a length of 20 mm in the rolling direction, which is the shooting range of the continuous photograph, is defined as "the distance between steps having a height difference of more than 5.0 μm on the steel sheet surface." Note that in this application, minute unevenness with a height difference of 1.0 μm or less is not considered to be a "step."

[0066] Furthermore, even if the steel plate has been formed or processed into some kind of component, by obtaining a part of the component after forming or processing (e.g., a flat part) and analyzing its surface condition, it is possible to determine whether the component had steps with a height difference of more than 5.0 μm at intervals of 2.0 mm or less when it was in the state of a steel plate before being formed or processed.

[0067] (Method of measuring tensile strength and total elongation) The tensile test for measuring the tensile strength and total elongation is performed in accordance with JIS Z 2241, using a JIS No. 5 test piece taken in such a way that the longitudinal direction of the test piece is parallel to the rolling direction perpendicular to the steel strip.

[0068] (Method of measuring hole expandability) The hole expandability is evaluated by punching a circular hole with a diameter of 10 mm under conditions where the clearance is 12.5%, forming it with a 60° conical punch so that the burr is on the die side, and measuring the hole expansion ratio λ (%). Five hole expansion tests are performed for each condition, and the average value is the hole expansion ratio.

[0069] (Method of measuring sliding friction resistance) The sliding friction resistance μ is determined by a flat plate pull-out test shown in Figure 3. A 10 mm wide test piece with a lubricant applied to its surface is clamped in a mold at a pressure of 20 MPa and pulled out 100 mm at a sliding speed of 100 mm / s. The average value of the sliding friction resistance when this is done is μ. The sliding friction resistance can be calculated as μ = F / 2P, where P is the pressing force and F is the pull-out load. The lubricant has a kinetic viscosity of 10 mm 2 A general lubricant with a concentration of 3.0 g / m2 is used. The amount of application is set to 3.0 g / m2 because the test must be performed with the lubricant stored within the unevenness of the steel sheet surface. 2 Let us assume that.

[0070] <Steel sheet manufacturing method> The method for producing a steel sheet according to this embodiment is characterized by the consistent management of hot rolling, cold rolling, and annealing using materials with the above-mentioned composition ranges. Specifically, the method for producing a steel sheet according to this embodiment is characterized by including the steps of hot rolling a steel piece (steel slab) having the same chemical composition as that described above for the steel sheet at a predetermined rolling reduction using a lubricant in a rolling mill one step before the final finishing rolling mill, coiling the resulting hot-rolled steel sheet, pickling it, cold rolling it, and then annealing it. More specifically, the method for producing a steel sheet according to this embodiment is characterized by the steps of: hot rolling the steel slab having the above chemical composition to obtain a hot rolled sheet; coiling the hot-rolled sheet; Pickling the hot-rolled sheet; and The method includes annealing the hot-rolled sheet without cold rolling, or annealing the hot-rolled sheet after cold rolling, The hot rolling includes rolling the plate at a reduction ratio of more than 30% and not more than 70% while supplying a lubricant between a rolling roll and the plate in a stand one before a final stand of a finishing mill; The temperature when the hot-rolled sheet is coiled is 700° C. or less, When the cold rolling is performed, the rolling reduction rate in the cold rolling is 0.1 to 20%. Each step will be described in detail below, focusing on the key points of this embodiment.

[0071] (Reduction rate at the stand before the final stand of the finishing mill) The reduction ratio at the stand immediately preceding the final stand of the finishing rolling mill is a factor that affects the surface condition of the steel sheet. Here, a lubricant (for example, an aqueous solvent mixed with a lubricant) is supplied to the rolled material (sheet) before rolling at the stand immediately preceding the final stand, and the sheet is rolled with high surface pressure while the lubricant remains on the sheet surface, thereby intermittently providing partial slip and contact between the sheet and the roll surface during rolling, thereby increasing the surface unevenness of the sheet. If the reduction ratio is too small, the surface pressure between the sheet and the roll during rolling is insufficient, and as a result, the desired surface unevenness cannot be formed on the steel sheet. Also, if the reduction ratio is too large, the surface pressure generated between the sheet and the roll during rolling becomes excessively high, and the frequency of contact rather than slip between the sheet and the roll increases, making it difficult to provide the desired surface unevenness to the finally obtained steel sheet. From the above viewpoints, in this embodiment, the reduction ratio in the stand immediately preceding the final stand of the finishing mill in hot rolling is more than 30% and not more than 70%, and preferably 35% or more and 60% or less. Note that it is difficult to perform a large reduction in the final stand of the finishing mill in order to correct the shape of the plate. The reduction ratio in the final stand of the finishing mill may be, for example, 20% or less.

[0072] In addition, it is possible to form a step on the surface of the hot-rolled steel sheet after finish rolling by controlling the cumulative reduction rate up to the final stand to be light reduction (for example, cumulative reduction rate of 20% or less) by supplying lubricant at a stand before the final stand. In this regard, the large reduction for increasing the surface unevenness of the sheet may be performed at a stand upstream of the stand immediately preceding the final stand. However, the sheet temperature is high on the upstream side of the finish rolling, and the shape of the sheet surface is easily changed by reduction. In other words, after the large reduction, it is necessary to control the cumulative reduction rate while taking into consideration the influence of temperature. In this regard, it is easier to form a desired step on the surface of the steel sheet by performing a large reduction of 30% or more while supplying lubricant at the downstream side of the finish rolling, particularly at the stand immediately preceding the final stand, and then performing a light reduction at the final stand to adjust the sheet shape.

[0073] Various lubricants can be used. For example, the lubricant may contain ester, mineral oil, polymer, fatty acid, S-based additive, or Ca-based additive. The viscosity of the lubricant is 250 mm. 2 The lubricant may be mixed with water as described above. The amount of lubricant supplied is not particularly limited. For example, the lubricant may be 0.1 g / m2 on the steel sheet surface. 2 or more than 1.0g / m 2 More than 100.0g / m 2 Less than or equal to 50.0 g / m 2 The following lubricants may be applied to the plate. The means for supplying the lubricant is not particularly limited, and the lubricant may be sprayed onto the plate surface, for example.

[0074] (Coil winding temperature) The temperature when the hot-rolled sheet is coiled (the coiling temperature of the hot-rolled coil) is a factor that controls the state of oxide scale formation in the hot-rolled sheet and affects the strength of the hot-rolled sheet. In order to maintain the surface unevenness generated by hot rolling, it is better for the thickness of the scale formed on the surface of the hot-rolled sheet to be thin, and therefore a low coiling temperature is preferable. In addition, when the coiling temperature is extremely reduced, special equipment is required. In addition, as described above, if the coiling temperature is too high, the oxide scale formed on the surface of the hot-rolled sheet becomes significantly thick, so that the convex parts of the unevenness formed on the surface of the hot-rolled sheet by hot rolling are incorporated into the oxide scale, and the scale is removed by the subsequent pickling, making it difficult to form the desired unevenness on the surface of the hot-rolled sheet. From the above viewpoints, the temperature when the hot-rolled sheet is coiled is 700°C or less, and may be 680°C or less, and may be 0°C or more, or may be 20°C or more.

[0075] (Reduction in cold rolling) The reduction ratio in cold rolling is an important factor for controlling the unevenness of the steel sheet surface as well as the shape of the hot rolled sheet. When cold rolling is performed, if the reduction ratio is too small, the shape defect of the hot rolled sheet cannot be corrected, and the curve of the steel strip remains, which may lead to a decrease in manufacturability in the subsequent annealing process. On the other hand, if the reduction ratio in cold rolling is too large, the convex parts of the unevenness formed on the surface of the hot rolled steel sheet by rolling are crushed by cold rolling, making it difficult to obtain the desired surface unevenness after the subsequent annealing. From the above viewpoints, when cold rolling is performed, the reduction ratio in the cold rolling is 0.1 to 20%. It is preferably 0.3% or more and 18.0% or less.

[0076] On the other hand, the hot-rolled sheet may be annealed as it is without cold rolling, which also makes it easier to obtain a steel sheet having the desired surface irregularities.

[0077] A preferred embodiment of the method for producing a steel sheet with minimal die damage during cold pressing will be described in detail below. The following description is an example of a preferred embodiment of hot rolling, heat treatment in annealing, plating treatment, etc., and does not limit the method for producing a steel sheet according to this embodiment.

[0078] (Hot rolling finishing temperature) The finish rolling temperature of hot rolling is a factor that has an effect on controlling the texture of the prior austenite grain size. From the viewpoint of developing the rolling texture of austenite and causing anisotropy in the steel material properties, the finish rolling temperature is preferably 650°C or higher, and from the viewpoint of suppressing the deviation of the texture due to abnormal grain growth of austenite, the finish rolling temperature is preferably, for example, 940°C or lower.

[0079] (Annealing holding temperature) It is important to control the maximum heating temperature to Ac3 point -20°C or higher in order to obtain a sufficient total area fraction of martensite and tempered martensite. If the temperature is less than Ac3 point -20°C, the total area fraction of martensite and tempered martensite decreases, making it difficult to ensure a tensile strength of 1300 MPa or more. On the other hand, excessive high temperature heating is not only economically undesirable because it increases costs, but also induces problems such as poor sheet shape during high-temperature sheet passing and reduced roll life, so the upper limit of the maximum heating temperature is preferably 900°C. The Ac3 point is calculated from the thermal expansion curve when a small piece taken from a cold-rolled steel sheet is heated to 900°C at 10°C / s.

[0080] (Annealing holding time) During annealing, it is preferable to hold the above heating temperature for 5 seconds or more. If the holding time is too short, the austenite transformation of the base steel sheet may not proceed sufficiently, resulting in a significant decrease in strength. In addition, the recrystallization of the ferrite structure becomes insufficient, and the hardness variation increases, resulting in a deterioration in hole expandability. From these viewpoints, the holding time is more preferably 10 seconds or more. More preferably, it is 20 seconds or more.

[0081] (Cooling rate after annealing) In the cooling after the annealing, it is preferable to cool from 750°C to the cooling stop temperature at an average cooling rate of 10°C / s or more and 100°C / s or less. The reason for setting the lower limit of the average cooling rate at 10°C / s is to suppress the softening of the steel sheet caused by the formation of ferrite, pearlite, and bainite during cooling. If the average cooling rate is slower than 10°C / s, the strength is significantly reduced. More preferably, it is 15°C / s or more, even more preferably 30°C / s or more, and even more preferably 50°C / s or more. Since ferrite transformation is significantly unlikely to occur at 750°C or more, the cooling rate is not limited. Since martensite is sufficiently formed at temperatures of 150°C or less, the cooling rate is not limited. Since cooling at a rate faster than 100°C / s tends to deteriorate the shape of the steel sheet, 100°C / s or less is preferable. More preferably, it is 90°C / s or less, and even more preferably, it is 80°C / s or less.

[0082] (Cooling stop temperature after annealing) The cold-rolled sheet annealing (cooling stop temperature) is 250°C or less. The cooling stop temperature is important for ensuring the total area ratio of martensite and tempered martensite. If the upper limit of the cooling stop temperature is 250°C or more, the martensite transformation is not completed sufficiently during cooling, so that the total area ratio of martensite and tempered martensite becomes less than 90%, and the strength is significantly reduced. It is preferably 200°C or less, more preferably 100°C or less. The lower limit of the cooling stop temperature is not particularly set, but is substantially 20°C or more.

[0083] (Tempering) After the cooling, the steel sheet may be retained for 2 seconds or more in a temperature range of 150°C or more and 400°C or less. According to this process, the martensite generated during cooling is tempered to form tempered martensite, thereby improving hydrogen embrittlement resistance. When the tempering process is performed, if the holding temperature is too low or the holding time is too short, the martensite is not sufficiently tempered, and there is almost no change in the microstructure and mechanical properties. On the other hand, if the holding temperature is too high, the dislocation density in the tempered martensite decreases, leading to a decrease in tensile strength. Therefore, when tempering is performed, it is preferable to hold the steel sheet for 2 seconds or more in a temperature range of 150°C or more and 400°C or less. Tempering may be performed in a continuous annealing facility, or may be performed offline after continuous annealing in a separate facility. In this case, the tempering time varies depending on the tempering temperature. That is, the lower the temperature, the longer the time, and the higher the temperature, the shorter the time.

[0084] (Skin pass reduction rate) Furthermore, skin pass rolling may be performed for the purpose of correcting the steel sheet shape and improving ductility by introducing mobile dislocations. The reduction ratio of the skin pass rolling after heat treatment is preferably in the range of 0.1 to 1.5%. If it is less than 0.1%, the effect is small and control is difficult, so this is the lower limit. If it exceeds 1.5%, the productivity drops significantly, so this is the upper limit. The skin pass may be performed inline or offline. In addition, the skin pass may be performed at the desired reduction ratio at one time, or may be performed in several steps. In addition, since the strength of the steel sheet after annealing is higher than that of the hot-rolled sheet, the change in the surface unevenness when rolling is performed at the same reduction ratio is not the same, but in order to maintain the unevenness formed by the hot-rolled sheet, the sum of the cold rolling rate and the skin pass rolling is preferably 20% or less.

[0085] According to the above manufacturing method, the steel sheet according to the above embodiment can be obtained. EXAMPLES

[0086] An embodiment of the present invention will be described below. The present invention is not limited to this example of conditions. The present invention can adopt various conditions as long as it does not deviate from the gist of the invention and achieves its object.

[0087] Steels having various chemical compositions were melted to produce steel billets. These billets were inserted into a furnace heated to 1220°C, and were subjected to homogenization treatment by holding them for 60 minutes, and then taken out into the air and hot-rolled to obtain steel plates with a thickness of 1.8 mm. In the hot rolling, a lubricant was supplied between the roll and the plate in the stand immediately preceding the final stand, and the rolling reduction, the finishing temperature (finishing temperature) of the finishing rolling in the stand immediately preceding the final stand of the finishing mill, and the coiling temperature of the hot-rolled coil were set to the values ​​shown in Tables 2-1 to 2-3 below. Subsequently, the oxide scale of the hot-rolled steel plates was removed by pickling, and the cold rolling was performed at the cold rolling reductions shown in Tables 2-1 to 2-3 below to finish the plate thickness to 1.4 mm. Furthermore, the cold-rolled steel plates were annealed and tempered under the conditions shown in Tables 2-1 to 2-3 below. Next, the cold-rolled steel sheets were subjected to skin-pass rolling at the rolling reductions (%) shown in Tables 2-1 to 2-3 below. The chemical compositions of samples taken from the obtained steel sheets were analyzed and are shown in Tables 1-1 to 1-6. The balance other than the components shown in Tables 1-1 to 1-6 is Fe and impurities.

[0088] The evaluation results of the properties of each steel sheet manufactured as described above are shown in the following Tables 3-1 to 3-3. In Tables 3-1 to 3-3, the measurement methods for "area ratio of the structure of the cold-rolled annealed sheet" and "properties (tensile strength, total elongation, hole expandability, interval of steps having a height difference of more than 5.0 μm on the sheet surface, sliding friction resistance)" are as described above.

[0089] [Table 1-1]

[0090] [Table 1-2]

[0091] [Table 1-3]

[0092] [Table 1-4]

[0093] [Table 1-5]

[0094] [Table 1-6]

[0095] [Table 2-1]

[0096] [Table 2-2]

[0097] [Table 2-3]

[0098] [Table 3-1]

[0099] [Table 3-2]

[0100] [Table 3-3]

[0101] The following can be seen from Tables 1-1 to 3-3.

[0102] No. 53 had a lower C content in the steel than the other examples, and the steel strength was slightly reduced.

[0103] No. 54 had too much C in the steel, which increased the steel strength but reduced the hole expandability. In addition, the surface of the steel sheet was significantly decarburized during hot rolling, and it is believed that the carbon atoms released from the steel surface in this decarburization reaction suppressed partial adhesion between the roll surface and the steel sheet surface, making it difficult to obtain the desired unevenness. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0104] In No. 55, the Si content in the steel was too high, which is believed to have caused coarse oxides to easily disperse in the surface layer of the hot-rolled sheet, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0105] In No. 56, the Mn content in the steel was too high, which led to a decrease in workability and, furthermore, it is believed that coarse oxides were easily dispersed in the surface layer of the hot-rolled sheet, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the finally obtained steel sheet, and the sliding friction resistance increased.

[0106] No. 57 had too much P in the steel, which caused the steel to break brittle and reduced elongation and hole expandability.

[0107] No. 58 had poor elongation and hole expandability due to the excessive S content in the steel. In addition, cracks were likely to occur originating from nonmetallic inclusions during hot rolling, and the cracks peeled off from the steel sheet during hot rolling, and the finely pulverized iron powder polished the steel sheet surface during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0108] In No. 59, the Al content in the steel was too high, and therefore the ferrite transformation and bainite transformation were accelerated during the cooling process of annealing, resulting in a decrease in the strength of the steel. In addition, it is believed that the surface of the steel sheet was polished during hot rolling due to the large amount of coarse Al oxides formed on the steel surface during hot rolling, which made it difficult to cause appropriate deformation during hot rolling and to obtain the desired unevenness. As a result, the desired unevenness could not be formed on the surface of the finally obtained steel sheet, and the sliding friction resistance increased.

[0109] In No. 60, the N content in the steel was too high, which caused excessive generation of nitrides in the steel, and the nitrides suppressed contact between the plate surface and the rolls during hot rolling, which is believed to have made it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0110] In No. 61, the Ti content in the steel was too high, which resulted in the excessive formation of coarse carbides in the steel, which in turn suppressed contact between the plate surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0111] In No. 62, the Co content in the steel was too high, which resulted in the excessive formation of Co carbides in the steel, which in turn suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0112] In No. 63, the Ni content in the steel was too high, which affected the peeling properties of the oxide scale during hot rolling and promoted the generation of scratches on the plate surface. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0113] In No. 64, the Mo content in the steel was too high, which resulted in the excessive formation of Mo carbides in the steel, which in turn suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0114] In No. 65, the Cr content in the steel was too high, which promoted the formation of retained austenite, and the presence of excessive retained austenite reduced the hole expandability.

[0115] No. 66 had poor hole expandability due to the excessive O content in the steel. In addition, coarse granular oxides were generated on the steel sheet surface, which led to cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0116] In No. 67, the B content in the steel was too high, which caused B oxides to form in the steel, and this B oxides suppressed contact between the sheet surface and the rolls during hot rolling, which is thought to have made it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0117] In No. 68, the Nb content in the steel was too high, which resulted in the formation of a large amount of Nb carbides in the steel, which suppressed contact between the plate surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0118] In No. 69, the V content in the steel was too high, which resulted in the formation of a large number of carbonitrides in the steel, which suppressed contact between the plate surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0119] In No. 70, the Cu content in the steel was too high, causing Cu to concentrate on the plate surface, which in turn suppressed contact between the plate surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0120] In No. 71, the W content in the steel was too high, which caused carbides to form in the steel, and the carbides suppressed contact between the plate surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0121] In No. 72, the Ta content in the steel was too high, which caused carbides to form in the steel, and the carbides suppressed contact between the plate surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0122] In No. 73, the Sn content in the steel was too high, which caused cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased. In addition, the excessive Sn content caused the steel sheet to become embrittled, and the hole expandability was reduced.

[0123] No. 74 had a low hole expandability because the Sb content in the steel was too high. It is also believed that this caused cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0124] No. 75 had poor hole expandability due to the excessive As content in the steel. It is also believed that this caused cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0125] In No. 76, the Mg content in the steel was too high, which resulted in poor hole expandability. In addition, coarse inclusions were formed in the steel, which suppressed contact between the plate surface and the roll during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0126] It is believed that No. 77 had an excessively high Ca content in the steel, which led to cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0127] In No. 78, the Y content in the steel was too high, which resulted in the formation of Y oxides in the steel, which suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0128] In No. 79, the Zr content in the steel was too high, which caused Zr oxides to form in the steel, and this Zr oxides suppressed contact between the sheet surface and the rolls during hot rolling, which is thought to have made it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0129] In No. 80, the La content in the steel was too high, which resulted in the formation of La oxides in the steel, which suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0130] In No. 81, the Ce content in the steel was too high, which caused Ce oxides to form in the steel, and the Ce oxides suppressed contact between the sheet surface and the rolls during hot rolling, which is believed to have made it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the sliding friction resistance increased.

[0131] In the case of No. 82, the reduction ratio in the stand before the final stand of the finishing mill was too small in hot rolling, which resulted in insufficient surface pressure between the plate and the rolls during hot rolling, making it difficult to form unevenness. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0132] In the case of No. 83, the reduction ratio in the stand before the final stand of the finishing mill was too large during hot rolling, which caused the surface pressure between the plate and the rolls to become excessively high during rolling, and this is believed to have increased the frequency of contact rather than sliding between the plate and the rolls. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0133] In No. 84, the temperature during coiling of the hot-rolled sheet was too high, so that the oxide scale formed on the surface of the hot-rolled sheet became extremely thick, and the convex parts of the unevenness formed on the surface of the hot-rolled sheet by hot rolling were incorporated into the oxide scale, and the convex parts were lost when the scale was removed by the subsequent pickling. As a result, the desired unevenness could not be formed on the surface of the finally obtained steel sheet, and the sliding friction resistance increased.

[0134] In No. 85, the reduction ratio in cold rolling was too large, so it is believed that the convex parts of the unevenness formed on the surface of the plate by hot rolling were flattened by cold rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0135] In No. 86, the desired surface unevenness could be formed on the steel sheet surface, and the sliding friction resistance could be reduced. However, the annealing temperature after cold rolling was too low, which reduced the area ratio of martensite and tempered martensite in the steel sheet, and the strength of the steel sheet was significantly reduced.

[0136] In No. 87, it is believed that in hot rolling, lubricant was not supplied to the stand one stand before the final stand of the finishing mill, which made it difficult for the plate to slip between the rolls. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the sliding friction resistance increased.

[0137] For Nos. 1 to 52 and 88, which had the content of each element within a specified range and were manufactured under specified manufacturing conditions, the desired structure was obtained in the final steel plate, and the desired unevenness was formed on the steel plate surface, resulting in increased sliding friction resistance.

[0138] From the above results, it can be said that a steel sheet satisfying the following requirements (I) to (III) has low sliding friction resistance, reduces damage to the die during cold pressing, and can extend the die life.

[0139] (I) By mass%, C: 0.15-0.35%, Si: 0.01-2.00%, Mn: 0.10-4.00%, P: 0.0200% or less, S: 0.0200% or less, Al: 0.001-1.000%, N: 0.0200% or less, Ti: 0-0.500%, Co: 0-0.500%, Ni: 0-0.500%, Mo: 0-0.500%, Cr: 0-2.000%, O: 0-0.0100%, B: 0-0.0100%, Nb: 0-0.500% , V: 0~0.500%, Cu: 0~0.500%, W: 0~0.1000%, Ta: 0~0.1000%, Sn: 0~0.0500%, Sb: 0~0.0500%, As: 0~0.0500%, Mg: 0~0.0500%, Ca: 0~0.0500%, Y: 0~0.0500%, Zr: 0~0.0500%, La: 0~0.0500%, and Ce: 0~0.0500%, with the remainder being Fe and impurities. (II) Having a steel structure consisting of, in terms of area ratio, the total of martensite and tempered martensite: 90.0% or more, the total of ferrite, pearlite and bainite: 0% or more and 10.0% or less, and retained austenite: 0% or more and 5.0% or less. (III) There are multiple steps on the plate surface with a height difference of more than 5.0 μm spaced apart by 2.0 mm or less.

[0140] It has also been found that a steel sheet satisfying the above requirements (I) to (III) can be manufactured by an integrated manufacturing method characterized by increasing the surface roughness of a hot-rolled sheet by adjusting hot-rolling conditions, and then passing through an annealing process without completely smoothing out the roughness. Specifically, it can be said that the steel sheet can be manufactured by the following manufacturing method. hot rolling the steel slab having the chemical composition of (I) to obtain a hot rolled sheet; coiling the hot-rolled sheet; Pickling the hot-rolled sheet; and Annealing the hot-rolled sheet without cold rolling, or annealing the hot-rolled sheet after cold rolling; Including, The hot rolling includes rolling the plate at a reduction ratio of more than 30% and not more than 70% while supplying a lubricant between a rolling roll and the plate in a stand one before a final stand of a finishing mill; The temperature when the hot-rolled sheet is coiled is 700° C. or less, When the cold rolling is performed, the rolling reduction rate in the cold rolling is 0.1 to 20%. Manufacturing method of steel plate.

Claims

1. In mass percent, C: 0.15-0.35%, Si: 0.01-2.00%, Mn: 0.10-4.00%, P: 0.0200% or less, S: 0.0200% or less, Al: 0.001-1.000%, N: 0.0200% or less, Ti: 0 to 0.500%, Co: 0 to 0.500%, Ni: 0 to 0.500%, Mo: 0-0.500%, Cr: 0-2.000%, O: 0 to 0.0100%, B: 0 to 0.0100%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0-0.500%, W: 0-0.1000%, Ta: 0-0.1000%, Sn: 0-0.0500%, Sb: 0 to 0.0500%, As: 0 to 0.0500%, Mg: 0 to 0.0500%, Ca: 0-0.0500%, Y: 0 to 0.0500%, Zr: 0 to 0.0500%, La: 0 to 0.0500%, and Ce: 0 to 0.0500%, and the balance being Fe and impurities, In terms of area ratio, Sum of martensite and tempered martensite: 90.0% or more, The sum of ferrite, pearlite and bainite: 0% or more and 10.0% or less, and Retained austenite: 0% or more and 5.0% or less, The steel structure comprises There are a plurality of steps having a height difference of more than 5.0 μm and not more than 20.0 μm on the plate surface at intervals of 2.0 mm or less, Tensile strength is 1300 MPa or more Steel plates (excluding hot-rolled steel plates).

2. In mass percent, Ti: 0.001 to 0.500%, Co: 0.001 to 0.500%, Ni: 0.001 to 0.500%, Mo: 0.001-0.500%, Cr:0.001~2.000% O: 0.0001-0.0100% B: 0.0001 to 0.0100%, Nb: 0.001-0.500%, V: 0.001-0.500%, Cu: 0.001 to 0.500%, W: 0.0001-0.1000%, Ta: 0.0001 to 0.1000%, Sn: 0.0001 to 0.0500%, Sb: 0.0001 to 0.0500%, As: 0.0001 to 0.0500%, Mg: 0.0001-0.0500%, Ca: 0.0001-0.0500%, Y: 0.0001-0.0500%, Zr: 0.0001 to 0.0500%, La: 0.0001 to 0.0500%, and Ce: 0.0001 to 0.0500%, The chemical composition contains one or more of the following: The steel sheet according to claim 1.

3. A method for manufacturing a steel sheet according to claim 1 or 2, hot rolling a steel slab having the chemical composition according to claim 1 or 2 to obtain a hot rolled sheet; coiling the hot-rolled sheet; Pickling the hot-rolled sheet; and Annealing the hot-rolled sheet without cold rolling, or annealing the hot-rolled sheet after cold rolling; Including, The hot rolling includes rolling the plate at a reduction ratio of more than 30% and not more than 70% while supplying a lubricant between a rolling roll and the plate in a stand one before a final stand of a finishing mill, The temperature when the hot-rolled sheet is coiled is 700° C. or less, When the cold rolling is performed, the reduction ratio in the cold rolling is 0.1 to 20%. Manufacturing method of steel plate.

Citation Information

Patent Citations

  • Steel sheet having excellent mold galling resistance

    JP1990037901A

  • Alloyed hot-dip galvanized steel sheet having excellent formability and brightness after painting

    JP1990274856A

  • Steel sheet for working having excellent painting brightness and production thereof

    JP1992253503A

  • Steel sheet for painting having excellent press formability

    JP1992333310A

  • Steel plate excellent in distinctness of coating and scratch resistance

    JP1993237505A